A Study on Uniqueness of Lip Print Patterns: Sexual Dimorphism, Twins, and Across Three Generations - Qudusia Sultana; Vanessa Fernandes; Ashwini Shetty (Archives of Medicine and Health Sciences)
Background and Aim: Lip prints just like fingerprints follow unique patterns in every individual and are said to vary significantly even within the same family. Lip prints can be recognized from 6th week of intrauterine life and remain unchanged throughout their life. The objective of the present study was to evaluate personal identification through lip print patterns with additional reference to twins and members of the same family. Materials and Methods: Lips of 75 males, 75 females, and 30 twins were studied in various quadrants. In addition, the pattern in the middle 10 mm of the lower lip was also evaluated to note the pattern distribution and dominance of the type of pattern in different genders. Lip print patterns in five families across three generations (eight members each of the same family) were observed for the existence of inheritance of patterns from their ancestors. Results: Among males and females, the most common pattern in the middle 10 mm of the lower lip is Type III (34.66%) and Type IV (32%), respectively. In the middle 10 mm of the lower lip, 33.33% of twins have similar lip patterns but with differences in its arrangements. The result showed different lip print patterns even in twins and among the members of the same family across three generations, with some similar patterns which suggesting hereditary influences in lip prints. Conclusion: In the present, we can see that lip prints are unique and permanent for every human being even among twins and individuals of the same family.